Induced Pluripotent Stem Cell-Differentiated Chondrocytes Repair Cartilage Defect in a Rabbit Osteoarthritis Model - Yu-Hsun Chang; Kun-Chi Wu; Dah-Ching Ding (Stem Cells International)
The aim of this study was to explore the therapeutic effect of iPSC-mesenchymal stem cell (MSC)-derived chondrocytes in a rabbit osteoarthritis (OA) model. The iPSCs were characterized by gene expressions, immunostaining of pluripotent markers, and in vivo teratoma formation. iPSC-differentiated MSCs were characterized by flow cytometry and trilineage differentiation. A rabbit OA model was established by the transection of the anterior cruciate ligament. The therapeutic effect of transplanted iPSC-MSC-chondrocytes on the OA was evaluated by the histology, immunostaining, and qPCR of defective cartilage. The results showed iPSC could express pluripotency markers such as OCT4, SOX2, and NANOG and form an embryoid body and a teratoma. After differentiation of iPSCs for 30 days, MSCs were established. The iPSC-MSC could express typical MSC markers such as CD29, CD44, CD90, CD105, and HLA-ABC. They could differentiate into adipocytes, osteocytes, and chondrocytes. In this model, iPSC-MSC-chondrocytes significantly improved the histology and ICRS (International Cartilage Repair Society) scores. The transplanted cartilage expressed less IL-1β, TNF-α, and MMP13 than control cartilage. In conclusion, the iPSCs we derived might represent an emerging source for differentiated MSC-chondrocyte and might rescue cartilage defects through its anti-inflammatory and anti-catabolic effects.